Effects of dietary lavender essential oil on growth performance, intestinal function, and antioxidant status of broiler chickens - Yarmohammadi Barbarestani, S.; Jazi, V.; Mohebodini, H.; Ashayerizadeh, A.; Shabani, A.; Toghyani, M. (Livestock science, 2020)
•Effects of dietary lavender essential oil (LEO) supplementation at 2 levels of 300 and 600 mg/kg was evaluated in a 42-d study.•Results indicated that supplementing the diet with 600 mg LEO/kg improved growth performance, intestinal mucosa morphology, and gut bacteria balance.•Dietary supplementation of LEO at both levels improved antioxidant status in serum and liver..•Dietary LEO supplementation (600 mg/kg of diet) can be used to replace antibiotic growth promoters in improving the productive performance of broiler chickens. A total of 480 one-day-old male broiler chickens were used in a 42-d study to assess the effects of different inclusion levels of lavender essential oil (LEO) supplementation in comparison with an antibiotic growth promoter on growth performance and physiological characteristics of broiler chickens. On d 1, broiler chickens were randomly assigned into 4 experimental treatments (6 replicates of 20 broiler chickens each) including a basal diet without any additive (control, CON), the basal diet supplemented with 200 mg/kg virginiamycin (VIM), and the basal diet supplemented with either 300 (LEO300) or 600 (LEO600) mg/kg LEO. The results showed that experimental treatments had no significant effect on feed intake at any stage of the study. In addition, no effect of experimental treatments was observed on body weight gain (BWG) and feed conversion ratio (FCR) over the starter period (d 0–21). However, broiler chickens fed diets supplemented with LEO600 and VIM had greater BWG and exhibited a lower FCR during grower (d 21–42) and the entire production period (d 0–42; P < 0.05). Likewise, feeding LEO600 and VIM diets decreased Escherichia coli population in the ileum and cecal contents and increased villus height and villus height to crypt depth of jejunum compared with the CON diet (P < 0.05). Dietary supplementation of LEO increased activity of superoxide dismutase in serum and liver and glutathione peroxidase activity in serum, but reduced concentrations of malondialdehyde in the serum (P < 0.05). In conclusion, addition of 600 mg/kg LEO to broiler chicken diets has the potential to improve growth performance, gut microbiota balance, intestinal morphology, and antioxidant activity.